Sistem Pendukung Keputusan Penentuan Stunting Di Gorontalo Menerapkan Metode Multi Attribute Utility Theory - Santawali; Muhammad Isla; Citra Yustitya Gobel (JSAI (Journal Scientific and Applied Informatics), 2024)
Stunting is the inability to grow and develop in toddlers caused by long-term malnutrition. This research aims to build a Decision Support System for Determining the Level of Stunting Susceptibility in Toddlers by analyzing the application of the Multi Attribute Utility Theory method to health services in Gorontalo. The urgency of this research is that the prevalence of stunting in Gorontalo Province is 23.8%, which is in the high category, stunting data at the end of December 2023 amounted to 4,545 children, therefore a support system is needed to determine the comprehensive and accurate level of stunting vulnerability of toddlers. so that you get the right treatment immediately. The research method used is Research and Development (R&D), which is a process for designing and developing a system that aims to support decision making regarding the prevention or handling of stunting. The results of system testing using the Whitebox method obtained V(G) = 2 and Cyclometic Complexity (CC) = 2 results and Independent Path results were R1 and R2 which can be concluded that the logic flow for the toddler value input module carried out by the nurse was effective and efficient. Meanwhile, the results of the Normalization Matrix Calculation and Utility Values on data for eight toddlers show that there are 5 toddlers who are determined to be vulnerable to stunting and 2 toddlers who are determined to be Not Susceptible to Stunting with a utility value of 0.23, the results of the calculation and aggregation of utility values are decided based on the Vulnerable category if the utility value is > 0.5 and Not Vulnerable if the utility value is <0.5. The results of the MAUT method allow each criterion to be given weight according to its relevance and contribution to stunting conditions, resulting in a more objective and structured evaluation in assessing stunting vulnerability